What does ahkam al-awqaf mean in cyprus? Reading a 2021 rule on endowments by the supreme court of northern cyprus from a comparative legal approach - BURSALI, OSMAN SAFA (My University, 2023)
In 2021, the High Court of Appeal of Cyprus (Yargıtay) referred an issue concerning Article 148 of the Constitution to the Supreme Court of Northern Cyprus (Yüksek Mahkeme). The parties to the case subject to the appeal were natural persons. A representative of the Attorney General’s Office of Cyprus as amicus curiae and a representative of the Administration of Endowments of Cyprus (Kıbrıs Evkaf İdaresi) attended the case.The plaintiffs filed a lawsuit against the defendants in the Girne District Court. They filed the appeal against the decision to dismiss and set aside this case. During the hearing of the appeal case, the plaintiffs/appellants demanded that the High Court of Appeal shall refer the matter to the Supreme Court. They argued that the legislation applied in the case before the lower court was unconstitutional. The High Court of Appeal evaluated the request and decided that the presented rule was a factor in the decision. As a result, the High Court of Appeal referred the matter to the Supreme Court for the following issues:- According to Article 149 of the Constitution of the Republic of Northern Cyprus,* The scope and nature of Ahkam al-Awqaf rules in Article 131 of the Constitution* Whether they are superior to other applicable laws* Whether the Ahkam al-Awqaf rules in force and recognized by the Constitution cover the amendments made before 1960* Interpretation of Article 131 as a whole;- To decide whether Articles 10 and 34 of Chapter 337 of the Law of Endowments violate Articles 1 and 131 of the Constitution.The Supreme Court reviewed the points mentioned by the High Court of Appeal.1) According to the first of the unanimous decisions, the Fundamental Rules on Endowments (Ahkam al-Awqaf), recognized by Article 131 of the Constitution, consists of the rules contained in the book Ahkamü’l-Evkaf, written by Ömer Hilmi Efendi and translated into English by C.R. Tyser and D.G. Demetriades.2) The Fundamental Rules on Endowments (Ahkam al-Awqaf) are legal sources that contain the rules to be applied related to endowments and endowed properties. (unanimous decision)3) Within the scope of the allegations made regarding Article 131 of the Constitution, Articles 10 and 34 of Chapter 337 of the Law of Endowments, which concerns only the case before the court, and on the condition that it is not related to the articles of the Constitution that make special provisions, the Fundamental Rules on Endowments (Ahkam al-Awqaf) rules are at the same level as the laws in force, including Chapter 337 on endowments. (unanimous decision)4) The Fundamental Rules on Endowments (Ahkam al-Awqaf) have not been changed by the legislation made before 1960 and are in force as they are in the book called Ahkamü\"l-Evkaf. (majority vote)5) Finally, Articles 10 and 34 of Chapter 337 of the Law of Endowments do not violate Article 131 of the Constitution. (unanimous decision)In this paper, I will discuss how Ahkamü’l-Evkaf is part of the legislation in force in Cyprus in light of the Supreme Court’s decision above. In this context, I will talk about the concept of \"the books of authority\" in the Common Law System and introduce the general structure of the book written by Ömer Hilmi Efendi. Next, I will analyze the aspects of Ahkamü’l-Evkaf in the Supreme Court’s decision. Finally, I will discuss the book’s place in Cyprus’ hierarchy of norms.
Keywords: Sosyal ve Beşeri Bilimler; Hukuk; Medeni Hukuk; Özel Hukuk; Social Sciences and Humanities; Law; Civil Law; Private Law; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; HUKUK; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; LAW; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities